1965
DOI: 10.1039/jr9650003433
|View full text |Cite
|
Sign up to set email alerts
|

621. Branched-chain sugars. Part III. The introduction of branching into methyl 3,4-O-isopropylidene-β-L-arabinoside and the synthesis ofL-hamamelose

Abstract: Branched-chain sugars have been synthesised by the following route : (i) protection of a methyl glycoside a t all sites except that a t which branching is to be introduced; (ii) oxidation of the unprotected hydroxyl group to obtain a protected methyl glycopyranosidulose ; (iii) treatment of the oxidation product with a Grignard reagent and removal of protecting groups. In this way methyl 3,4-O-isopropylidene-~-~-erythro-pentopyranosidulose has been prepared and treated with a range of Grignard reagents, and, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…with Varían T-60 and HR-220 spectrometers using tetramethylsilane as an internal standard. Chemical shifts (5) are expressed in parts per million. The proton noise decoupled carbon-13 nmr spectra were recorded with a TNM PS-100 FT spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…with Varían T-60 and HR-220 spectrometers using tetramethylsilane as an internal standard. Chemical shifts (5) are expressed in parts per million. The proton noise decoupled carbon-13 nmr spectra were recorded with a TNM PS-100 FT spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…9 We now wish to report the results of our studies on the addition of methylmagnesium halides and methyllithium to the methyl a-D-xyio-hexopyranosid-4-uloses 1 and 2, and on the application of the carbon-13 nmr spectroscopy for configurational assignments at the thus created branching carbon atom. Methyl 2,3-di-0-methyl-6-0-triphenylmethyl-«-D-xy/ohexopyranosid-4-ulose (1) and methyl 3-0-methyl-2-0me thy lsulfony 1-6-0-tr iphenylmethyl-n-D-xy/o-hexopyranosid-4-ulose (2) were synthesized by the oxidation of methyl 2,3-di-0-methyl-6-0-triphenylmethyl-«-D-glucopyranoside (4) and methyl 3-0-methyl-2-0-methylsulfonyl-6-O-triphenylmethyl-a-D-glucopyranoside (5) with dimethyl sulfoxide-acetic anhydride at 50-60°.…”
mentioning
confidence: 99%
“…144°C; [a]D +41" (c 1.5); vmax. 3 Jdax.5eq 3.0 Hz, 4-Hax), and 1-74 (1 H, m, J4eq.4ax 13-87 J4eq.3 2-87 J 4 e q , ~e q 2-87 J4eq.sax 2. 5 Hz, 4-Heq), and 5-He,), 3.44 (3 H, s, OMe), 2.12 (1 H, m, J4ax,4eq 13.8, (Found: C , 61.2; H, 6.8; N , 5.6.…”
Section: Methyl 3-benzamido-2-o-benzoyl-34-dideoxy-a-~-ery T Hropento...mentioning
confidence: 97%
“…of this component is approximately five times greater for 1-H than for 3-H it was concluded that this isomer is the ' syn ' form of the phenylhydrazone (3).' (For the convention of assignment of ' syn ' and ' anti ' forms, see ref.…”
mentioning
confidence: 99%
“…Sharpless epoxidation of the enynols 83a and 83b. By Addition to CwO Groups About 50 publications dealing with the addition of acetylenes to aldosulopyranosides and -furanosides have been published since the first reports by Overend and co-workers in 1965 and 1970[155]. Mixtures of epimeric propargylic alcohols are expected, but the (mostly steric) influence of adjacent substituents may give diastereoselective addition.…”
mentioning
confidence: 99%